HIV-1 Infection Is Associated With Increased Prevalence and Abundance of Plasmodium falciparum Gametocyte-Specific Transcripts in Asymptomatic Adults in Western Kenya - Stiffler, Deborah M.; Oyieko, Janet; Kifude, Carolyne M.; Rockabrand, David M.; Luckhart, Shirley; Stewart, V. Ann (Frontiers in Cellular and Infection Microbiology, 2021)
As morbidity and mortality due to malaria continue to decline, the identification of individuals with a high likelihood of transmitting malaria is needed to further reduce the prevalence of malaria. In areas of holoendemic malaria transmission, asymptomatically infected adults may be infected with transmissible gametocytes. The impact of HIV-1 on gametocyte carriage is unknown, but co-infection may lead to an increase in gametocytemia. In this study, a panel of qPCR assays was used to quantify gametocyte stage-specific transcripts present in dried blood spots obtained from asymptomatic adults seeking voluntary HIV testing in Kombewa, Kenya. A total of 1,116 Plasmodium-specific 18S-positive samples were tested and 20.5% of these individuals had detectable gametocyte-specific transcripts. Individuals also infected with HIV-1 were 1.82 times more likely to be gametocyte positive (P<0.0001) and had significantly higher gametocyte copy numbers when compared to HIV-negative individuals. Additionally, HIV-1 positivity was associated with higher gametocyte prevalence in men and increased gametocyte carriage with age. Overall, these data suggest that HIV-positive individuals may have an increased risk of transmitting malaria parasites in regions with endemic malaria transmission and therefore should be at a higher priority for treatment with gametocidal antimalarial drugs.